Cost-effectiveness of tocilizumab, a humanized anti-interleukin-6 receptor monoclonal antibody, versus methotrexate in patients with rheumatoid arthritis using real-world data from the IORRA observational cohort study. Issue 4 (July 2015) - Tanaka, Eiichi; Inoue, Eisuke; Hoshi, Daisuke; Shimizu, Yoko; Kobayashi, Akiko; Sugimoto, Naoki; Shidara, Kumi; Sato, Eri; Seto, Yohei; Nakajima, Ayako; Momohara, Shigeki; Taniguchi, Atsuo; et al.
Abstract Objectives. To evaluate the cost-effectiveness of tocilizumab in patients with rheumatoid arthritis (RA) in a real-world setting in Japan. Methods. The cost-effectiveness was determined using a Markov model-based probabilistic simulation. Data from RA patients registered in the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) cohort study between April 2007 and April 2011 were extracted using a pair-matching method: tocilizumab group (n = 104), patients who used at least 1 disease-modifying anti- rheumatic drug and in whom tocilizumab treatment was initiated; methotrexate group (n = 104), patients in whom methotrexate treatment was initiated for the first time or after an interruption of 6 or more months. Assuming a 6-month cycle length, health benefits and costs were measured over a lifetime and discounted at an annual rate of 3%. Results. Compared with methotrexate treatment, lifetime costs and quality-adjusted life years (QALYs) for tocilizumab treatment were approximately 1.5- and 1.3-times higher, respectively. Incremental cost per QALY gained with tocilizumab was $49, 359, which was below the assumed cost-effectiveness threshold of $50, 000 per QALY. The probability of tocilizumab being cost- effective was 62.2%. Conclusion. The simulation model using real-world data from Japan showed that tocilizumab (at a certain price) may improve treatment cost-effectiveness in patients with moderate-to-severe RA by enhancing quality-adjusted life expectancy.